1977
DOI: 10.1136/bjsm.11.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting performance during an endurance relay.

Abstract: A successful attempt by Edinburgh Athletic Club on the world record for the 24-hour 10-man x 1 mile relay is reported. The effects of a variety of factors on the performances of the athletes are assessed, and some physiological changes noted. In the light of these observations recommendations are made to help the planning of future record attempts. to the time required each runner would be given massage 138 copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, with the exception of the studies in *To whom all correspondence should be addressed. runners (Lloyd et al, 1977;O'Hara et al, 1977 andThompson, 1979) and soccer players (Reilly and Walsh, 1981), there has been little attention to the study of extreme endurance performance under actual competitive conditions. Furthermore, even in these most recent studies the emphasis has been largely upon the work performance demands rather than the nutritional requirements of the event Therefore in view of the increasing popularity of "ultra-distance" competitive events but relative lack of attention focused upon the study of the specific demands of such activity, the present investigation was undertaken in order to estimate the relative aerobic demand, energy expenditure and nutritional intake of a racing cyclist involved in a 24 h road race event.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the exception of the studies in *To whom all correspondence should be addressed. runners (Lloyd et al, 1977;O'Hara et al, 1977 andThompson, 1979) and soccer players (Reilly and Walsh, 1981), there has been little attention to the study of extreme endurance performance under actual competitive conditions. Furthermore, even in these most recent studies the emphasis has been largely upon the work performance demands rather than the nutritional requirements of the event Therefore in view of the increasing popularity of "ultra-distance" competitive events but relative lack of attention focused upon the study of the specific demands of such activity, the present investigation was undertaken in order to estimate the relative aerobic demand, energy expenditure and nutritional intake of a racing cyclist involved in a 24 h road race event.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that work can be sustained at a high intensity over this period. Lloyd et al (1977) reported proteinuria in athletes attempting a 24 h relay run world record. With work intensity reduced to a constant oxygen uptake demand of 15 ml/kg/min'1 Thomas and Reilly (1975) reported that exercise can be continued for up to 100 h under conditions of controlled energy intake.…”
Section: Introductionmentioning
confidence: 99%